ROCK TYPE DETERMINATION AND PERMEABILITY PREDICTION IN WIDURI FIELD - AFIANTY (NIM: 22208012), ANISA
Permeability is one of petrophysics parameter which very important to be known from a reservoir but difficult to be determined. Pore architecture, both geometry and structure, is very affecting the rock permeability so can be used to predict the permeability. Pore geometry and structure can be used also in doing rock type determination. Permeability and rock type will be useful in reservoir characterization and development, and will be helpful to build geological model to do dynamic reservoir analysis or reservoir simulation. The objectives of this research are to improve a method to identify rock type based on relationship between pore geometry and pore structure, and to improve a method to predict permeability with considering geological aspect. Core data from Widuri-01 well with a total length of 263 ft and 127 core plugs, each of them is measured for its porosity and permeability, combined with log data are used in this study. Rock type determination is done by making Pore Geometry-Structure (PGS) plot, which is plot between ()5,0/φk as pore geometry parameter and 3/φk as pore structure parameter. Permeability prediction is done by making permeability equation as a function of porosity and water saturation for each rock type. Reservoir in Widuri-01 can be divided to six rock type which in association with the facies. Each of rock type has permeability equation as a function of porosity and water saturation which has been validated in Widuri-10. These equations can be used to predict permeability in un-cored wells as long as log data is available and facies or rock type is known.